2012
DOI: 10.1002/art.33399
|View full text |Cite
|
Sign up to set email alerts
|

T cell protein tyrosine phosphatase deficiency results in spontaneous synovitis and subchondral bone resorption in mice

Abstract: Objective. T cell protein tyrosine phosphatase (TC-PTP) is an important regulator of hematopoiesis and cytokine signaling. Recently, several genome-wide association studies have identified single-nucleotide polymorphisms (SNPs) in the locus of TC-PTP that are associated with rheumatoid arthritis and juvenile idiopathic arthritis, among other autoimmune diseases. The aim of this study was to evaluate the effect of TC-PTP deficiency on the bone and joint environment using a knockout mouse model.Methods. Radiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
4
12
0
1
Order By: Relevance
“…Previous work had demonstrated a cell-autonomous function of TC-PTP in hematopoietic cell differentiation (42,43). Mice lacking TC-PTP globally exhibit an increase in osteoclast density and bone resorption (15). The current work expands the importance of TC-PTP by showing that it is able to regulate differentiation cell nonautonomously.…”
Section: Discussionsupporting
confidence: 57%
“…Previous work had demonstrated a cell-autonomous function of TC-PTP in hematopoietic cell differentiation (42,43). Mice lacking TC-PTP globally exhibit an increase in osteoclast density and bone resorption (15). The current work expands the importance of TC-PTP by showing that it is able to regulate differentiation cell nonautonomously.…”
Section: Discussionsupporting
confidence: 57%
“…Other protein tyrosine phosphatases were reported to play a regulatory role in inflammation (20). For example, loss of T cell protein tyrosine phosphatase expression results in synovitis, with several hallmarks of inflammatory arthritis, within mouse femurs (21). In the current study, we demonstrated that PTPRO is a critical regulator in both human and mouse FH.…”
Section: Discussionsupporting
confidence: 60%
“…Our data suggest that balanced nonpathological T helper polarisation requires a highly upregulated expression of SHP1 during the generation of IFN γ producing cells. By contrast, although the polymorphism rs1893217(C) in the PTPN2 gene has been associated with a decrease in the expression levels that promotes autoimmunity [23, 70] and to a reduced response to IL-2 [26], the regulation of the expression levels of this gene does not seem to be necessary during the generation of IFN γ producing cells. Single nucleotide polymorphisms (SNPs) in nonregulated PTPs PTPN22 and PTPRC have been associated with human autoimmune diseases, including multiple sclerosis and autoimmune hepatitis in the case of PTPRC and type I diabetes, rheumatoid arthritis, and systemic lupus erythematosus in the case of PTPN22 [13, 23, 37, 52].…”
Section: Conclusion: Perspective On Autoimmune Diseasesmentioning
confidence: 99%